Evaluation of the holding-up uterus technique for placenta accreta spectrum cesarean hysterectomy in shocked patients with a high shock index: a case series study - Jin Takahashi; Makoto Orisaka; Daisuke Inoue; Hiroshi Kawamura; Nozomu Takahashi; Hideaki Tsuyoshi; Akiko Shinagawa; Tetsuji Kurokawa; Yoshio Yoshida (BMC Surgery, 2024)
Abstract Background Placenta accreta spectrum (PAS) cesarean hysterectomy is performed under conditions of shock and can result in serious complications. This study aimed to evaluate the usefulness of the “Holding-up uterus” surgical technique with a shock index (S.I.) > 1.5. Methods Twelve patients who underwent PAS cesarean hysterectomy were included in the study. Results Group I had S.I. > 1.5, and group II had S.I. ≤ 1.5. Group I had more complications, but none were above Grade 3 or fatal. Preoperative scheduled uterine artery embolization did not result in serious complications, but three patients who had emergency common iliac artery balloon occlusion (CIABO) and a primary total hysterectomy with S.I. > 1.5 had postoperative Grade 2 thrombosis. Two patients underwent manual ablation of the placenta under CIABO to preserve the uterus, both with S.I. > 1.5. Conclusions The study found that the “Holding-up uterus” technique was safe, even in critical situations with S.I. > 1.5. CIABO had no intervention effect. The study also identified assisted reproductive technology pregnancies with a uterine cavity length of less than 5 cm before conception as a critical factor.